Peran Mahasiswa KKN dalam Menyediakan Bimbingan Belajar untuk Mendukung Pendidikan Anak di Desa Bukit Harapan - Desri Nora AN; Alwi Abrar Rusli; Fadhilah Gusti; Fitri Ramadhani; Rizqia Salsabillah (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
The Community Service Program (KKN) serves as a strategic platform for university students to contribute to community education. This article describes the role of students from Universitas Negeri Padang in providing tutoring sessions for children in Bukit Harapan Village during school holidays. The non-formal learning activities were designed to fill children's free time with educational content such as reading, writing, arithmetic, basic English, music, poetry, and traditional dance. This research used a descriptive qualitative method with participatory observation. Results show that the program enhanced children’s basic academic skills, creativity, and self-confidence. The main challenges faced included limited learning resources, diverse student abilities, and the short duration of the program. Nevertheless, the program proved effective in supporting children's education and empowering rural communities.